The role of ethics and social responsibility in achieving organizational effectiveness: Students versus managers - Kraft, Kenneth L. (Journal of business ethics, 1991)
This paper investigates the differences in perceptions between business students and service-sector managers regarding the role that ethics and social responsibility serve in determining organizational effectiveness. An organizational effectiveness instrument containing business ethics and social responsibility items served as a questionnaire for a sample of 151 senior business undergraduates and 53 service-sector managers. The results indicated that while students acting as managers rate some social responsibility issues as more important than do managers, they also rate ethical conduct and a few dimensions of social responsibility lower than do managers. The findings have direct implications for both business practitioners and educators.